Kelimpahan Dan Pola Pertumbuhan Kerang Bulu (Anadara antiquata) di Perairan Gunung Riting Kabupaten Belitung - Ardiansah, Nopal; Yusanti, Indah Anggraini; Anwar, Syaeful (Universitas PGRI Palembang, 2024)
Gunung Riting waters are located in Belitung Regency which has high water biota resource potential. One biota that has a high economic value is the feather shell (Anadara antiquata). Feather shells generally live in muddy waters in shallow waters with a high turbidity levels and are one of the important commodities that are very potentially developed. The purpose of this study was to find out the abundance, growth patterns and water quality in the waters of gunung which is the habitat of feather shells. The study was conducted from December 2019 to January 2020 at 3 sampling stations, sampling using the transect method. The results of the study obtained that the highest number of feather shells found in the waters of gunung riting obtained at Station 2 is 506 feather shells with an abundance of 33.73 individuals/m2, the pattern of growth of feather shells in the waters of gunung riting has an negative allometric growth pattern where long growth is more dominant than weight growth and the water quality obtained is able to support the growth and abundance of feather shells in the waters of gunung riting.